George, the dragon and the princess - Wormell, Christopher (UK : Red Fox, 2008)
A little mouse named George is not good at very many things, but his talent at scaring a threatening dragon helps him to make a new friend.
2.3
K-3.
K-3
Keywords: Dragons -- Juvenile fiction; Mice -- Juvenile fiction; Dragons -- Fiction; Mice -- Fiction; Dragons -- Fiction; Mice -- Fiction